Acquisitions as a response to deregulation: Evidence from the cable television industry - David P. Byrne (Queen's University, Department of Economics, 2010)
This paper studies the dynamics of an industry that is subject to exclusive geographical licensing. I develop a model of license ownership that predicts the evolution of profit-maximizing entry and acquisition decisions by firms over time, starting from an initial allocation of licenses. The entry and acquisition process is modeled as a one-sided coalition-formation game as in Farrell and Scotchmer (1988), where acquisition payoffs depend on economies of scale and agglomeration (economies of density). I estimate the model for the cable television industry in Canada using a panel that I have constructed from 1990 to 1996. The dataset builds up from the national regulator's license-ownership decision files, and contains license-level information on acquisition decisions, subscribership, and subscription profits. The model is estimated in two steps. I first estimate firms' license-level profit functions, and then estimate the parameters of the fixed, merger and entry cost functions by Simulated Maximum Likelihood. Through counterfactual simulations, I use the estimated model to quantify the extent to which economies of scale and density drive acquisition behaviour, and to evaluate how merger activity reacts to a partial deregulation that occurs in 1994. Counterfactual experiments are also used to evaluate policies that stimulate entry or reduce acquisitions in the early years of the sample. The main finding is that these policies can lead to more productive dominant firms in the long-run as the industry consolidates.
Keywords: L12; L22; 330; Acquisition; Entry; Coalition Formation; Economies of Density; Economies of Scale; Simulated Maximum Likelihood; Cable Television; Strategisches Management; Betriebliche Forschung; Patent; Markteintritt; Übernahme; Kabelfernsehen; Maximum-Likelihood-Methode; Kanada